Vici Syndrome: A Rare Autosomal Recessive Syndrome with Brain Anomalies, Cardiomyopathy, and Severe Intellectual Disability - R. Curtis Rogers; Bridgette Aufmuth; Stephanie Monesson (Case Reports in Genetics)
Purpose. The objective of this study was to present and describe two additional patients diagnosed with Vici syndrome. Methods. Clinical, laboratory, and imaging findings of the two siblings are discussed in detail. The two patients' descriptions are compared with the other eleven patients reported in the literature. We also presented detailed autopsy results on the male sibling, which demonstrated cytoplasmic vacuoles of the cardiomyocytes and confirmed the clinical findings. Results. The patients reported here include the 13th and 14th patients reported with Vici syndrome. The summary of findings present in these patients includes postnatal growth retardation, developmental delay, bilateral cataracts, agenesis of the corpus callosum, cerebellar anomalies, gyral abnormalities, seizures, hypotonia, and cardiomyopathy. Conclusion. Vici syndrome should be suspected in any child with agenesis of the corpus callosum and one of the following findings: cardiomyopathy, cataracts, immune deficiency, or cutaneous hypopigmentation.